2007
DOI: 10.5195/jyd.2007.349
|View full text |Cite
|
Sign up to set email alerts
|

Camp Counseling and the Development and Transfer of Workforce Skills: The Perspective of Ohio 4-H Camp Counselor Alumni

Abstract: Recent research shows that camp counselors, including those in 4-H, benefit from the experience by developing important life skills. However, because research regarding the perception of workforce skill development in this context has yielded inconsistent findings, the present study used focus groups to examine 4-H camp counselor alumni perceptions about the skills gained and transfer of these skills to other settings. Overall, 4-H camp counselor alumni thought their experience was fun and enjoyable, yet chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…41 Young adults who have worked at camp also appear to gain skills that affect their personal relationships, careers, and civic engagement outside camp. Two studies that focused on the long-term impacts of working at camp found that alumni staff believed that camp experiences contributed to twenty-fi rst-century workforce skills such as planning, decision making, communication, and teamwork, 42 and that these experiences helped them explore new opportunities and try out new roles that they could apply in other settings. 43 Given the expansion of the definition of adolescence into the mid-to late twenties, many camp staff are in a developmental life stage much like the campers they serve.…”
Section: Staff Developmental Outcomesmentioning
confidence: 99%
“…41 Young adults who have worked at camp also appear to gain skills that affect their personal relationships, careers, and civic engagement outside camp. Two studies that focused on the long-term impacts of working at camp found that alumni staff believed that camp experiences contributed to twenty-fi rst-century workforce skills such as planning, decision making, communication, and teamwork, 42 and that these experiences helped them explore new opportunities and try out new roles that they could apply in other settings. 43 Given the expansion of the definition of adolescence into the mid-to late twenties, many camp staff are in a developmental life stage much like the campers they serve.…”
Section: Staff Developmental Outcomesmentioning
confidence: 99%
“…Studies about 4-H camp counselors in other states found that counselors could identify at least one skill that was developed as a result of camp counseling that would help them in a job they desired in the future (Forsythe et al, 2004), the camp counseling experience provides an opportunity to learn about potential future careers (Digby & Ferrari, 2007), and camp counseling can highly influence career choice of counselors (Genson, 2010 reason could be that some of the counselors have already selected a career path. Participants in the survey were never asked why they wanted to serve as counselors, but three of the top five statements in this construct had a social dimension; counselors enjoyed working with children, meeting new people, and improving their ability to work with children.…”
Section: Journal Of Human Sciences and Extensionmentioning
confidence: 99%
“…Ohio 4-H camp counselor alumni also listed improved planning and organizing, decision making, and interpersonal skills as significant outcomes of the camp counseling experience (Digby & Ferrari, 2007).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This research indicates that significant benefits exist for teens who lead camps, including increased leadership skills, sense of responsibility, connection with campers, and a sense of community contribution Bird & Subramaniam, 2011;Brandt & Arnold, 2006;Garst & Johnson, 2005;Nicholson & Klem, 2016;Tessman, Duda, & Pracht, 2012). In addition, researchers have shared how camp experiences translate to workforce and career preparedness for teens (Digby & Ferrari, 2007).…”
Section: Prior Research On Teen Staff Experience and Outcomes At Campmentioning
confidence: 91%